Personality traits and scholastic cheating in a student population: exploring whether personality is a predictor of scholastic cheating using the HEXACO-60 and Dark Triad (DT) - Cheung, Yuen Kiu (2019)
Previous studies have found inconsistent results regarding the personality predictors of scholastic cheating. The aim of this study was to investigate whether personality was a predictor of scholastic cheating using the HEXACO-60 personality inventory and the Dark Triad (DT). A sample of 252 students completed the online questionnaire. Results from a one-way ANOVA showed that scholastic cheating was more common in associate degree/diploma/foundation students and undergraduate students than postgraduate students. Year of study or student status (local or international students) had no effect on scholastic cheating. MANOVA showed that academic qualification, year of study, and student status had no effect on reasons for cheating. A hierarchical regression found that conscientiousness was a significant negative predictor of scholastic cheating whereas Machiavellianism and psychopathy were significant positive predictors of scholastic cheating. Psychopathy emerged as the strongest significant predictor of scholastic cheating. These results supported the view that personality is relevant for understanding scholastic cheating; a positive personality trait - high conscientiousness - predicted less scholastic cheating whereas negative personality traits - high Machiavellianism and psychopathy predicted more scholastic cheating. Students characterized by cynicism, manipulation, high impulsivity, and a lack of empathy have a higher likelihood in engaging scholastic cheating.